Analysis of heat sink effect in hepatic cancer treatment near arterial for microwave ablation by using finite element method - P. Yhamyindee (2018)
This paper presents an analysis of heat sink effect in hepatic cancer treatment near arterial vessel for microwave ablation by using finite element method. We analyze the temperature distribution, Specific Absorbtion Rate (SAR) and coagulation area in two models. The first is hepatic tissue without artery and the second is hepatic tissue with artery. In the second model, we specify distance between antenna and artery at 10 mm. The initial condition is set as power at 50 watts, temperature at 37°C and blood perfusion rate is varied at 6.4 × 10 -10 , 6.4 × 10 -3 and 6.4 × 10 4 l/s. The simulation results by using three-dimensional finite element analysis show that the temperature distribution in case of hepatic tissue with no artery is larger than the case with artery. We also found that blood perfusion rate affects to the temperature distribution in hepatic tissue. Higher blood perfusion rate, higher heat sink effect occur. ©2012 IEEE.